Can a sense of belonging influence institutional attachment among first-year university students? Assessing the moderated mediation effects of social and emotional adjustment - Bongani Mtshweni (Journal of Student Affairs in Africa, 2025)
The study investigated the relationship between sense of belonging and institutional attachment and the moderated mediation effects of social and emotional adjustment. The study comprised 209 first-year students from a South African university (Mean = 25,42 years, SD = 6.19). Using a quantitative research approach to inquiry, the multiple linear regression and moderated mediation analyses showed that sense of belonging significantly predicted institutional attachment. Additionally, the results showed that social adjustment significantly mediated the relationship between sense of belonging and institutional attachment. Furthermore, the results revealed that the moderated mediation effects of social and emotional adjustment were statistically insignificant. The results accentuate that sense of belonging is crucial for enabling institutional attachment towards university, underscoring the importance of striving for university environments that are belonging-centred to help first-year students identify with their learning contexts.